Red Fox Use of Landscapes with Nesting Shorebirds. Issue 8 (1st September 2020) - Stantial, Michelle L.; Cohen, Jonathan B.; Darrah, Abigail J.; Farrell, Shannon; Maslo, Brooke
ABSTRACT: Predation of nests and young is one of the limiting factors in the conservation of birds; understanding environmental covariates of predator distribution can assist with decisions regarding the best management strategies to reduce predation risk. The habitat of beach‐nesting birds is often reshaped by storms in ways that may affect nest predation, such as by flattening vegetated dunes where mammals hunt, but human management of beaches tries to prevent the effects of storms on the landscape with unknown implications for predator distributions. Moreover, human development may affect predator distributions by subsidizing food and shelter. To determine the relationship between predator occupancy and landscape features in beach‐nesting bird habitat, we repeated mammalian predator track surveys 8 times/year at 90 plots in southern New Jersey, USA, from 2015–2017. We used dynamic occupancy models to estimate the probability of use by red foxes ( Vulpes vulpes ) and to document changes in habitat use as related to landcover types over the avian breeding season within years. We had 373 red fox detections with years pooled. Detection probability for red foxes varied by year, and probability of use decreased as the distance to the nearest primary dune increased. We found no evidence that red fox habitat use depended on distance to human development. Our results suggest that conserving nesting habitat that includes open areas (i.e., storm overwash [whereby vegetation is scoured by tidal flooding]) may reduce predation risk because beach‐nesting birds would not be forced into nesting close to dunes, which are typically used for hunting by red foxes. © 2020 The Wildlife Society. Abstract : Conserving nesting habitat that includes overwash fans and sparsely vegetated areas may improve nest success of piping plovers because birds are not forced into nesting in areas typically used for hunting by red foxes, which are close to primary dunes. Piping plovers are dependent on patchy dunes that are separated by open areas of overwash for breeding and management that maintains the heterogeneity created by coastal storms is important for successful nesting both in terms of foraging quality and predation risk.